2017
DOI: 10.4314/bcse.v30i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pb(II) ions from aqueous solution using lignin from Hagenia abyssinica

Abstract: ABSTRACT. The adsorption of lead(II) ions from aqueous solution onto alkali lignin extracted from Hagenia abyssinica was investigated by electrochemical methods. The effect of solution pH, lignin dosage and contact time were investigated at room temperature in a batch system. Adsorption equilibrium was approached within 80 min. The adsorption kinetics data were described by pseudo-second-order kinetics model, while the equilibrium data were well fitted using the Freundlich model. A maximum adsorption capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In most references, Freundlich adsorption Eq. (5) may also be expressed as ln q e = ln K F +1/n C e (6) All the correlation coefficients, R 2 value, and the constants obtained for the models show that the Langmuir and Freundlich isotherms fitted with cadmium(II) and only Freundlich isotherm fitted with lead(II) and copper(II) ions. Freundlich isotherm is suitable equation to describe the adsorption equilibrium of heavy metals (Pb, Cd, Cu) on the Cr doped NiO (Figure 9).…”
Section: Freundlich Isothermmentioning
confidence: 95%
See 1 more Smart Citation
“…In most references, Freundlich adsorption Eq. (5) may also be expressed as ln q e = ln K F +1/n C e (6) All the correlation coefficients, R 2 value, and the constants obtained for the models show that the Langmuir and Freundlich isotherms fitted with cadmium(II) and only Freundlich isotherm fitted with lead(II) and copper(II) ions. Freundlich isotherm is suitable equation to describe the adsorption equilibrium of heavy metals (Pb, Cd, Cu) on the Cr doped NiO (Figure 9).…”
Section: Freundlich Isothermmentioning
confidence: 95%
“…Their presence even in low concentration in water is harmful to human health as well as aquatic life. Lead is a heavy metal and commonly used in households and many industries [4][5][6]. Thus industrial wastewater is considered to be a potential source of trace metal pollution [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The water, appears in Figure (2), contains different type of pollutants such as organic, inorganic, heavy metals, pesticides, dyes, phenols, and many other pollutants [6][7][8][9]. These pollutants change the water physical properties like change its odor, color, and taste.…”
Section: Types Of Water Pollutantsmentioning
confidence: 99%
“…The method was successfully applied to determine heavy metals in different samples like vegetables ( Xu et al, 2008a ), wine ( Kefala et al, 2004 ), urine ( Kefala et al, 2004 ), human hair ( Kefala, 2003 ), medicinal plants ( Xu et al, 2008b ) and milk ( Ping et al, 2014 ). In our recent work ( Tesfaw et al, 2016 ), ASV using BiFE was demonstrated for studying the adsorption behavior of lead ions onto a natural biopolymer without requiring the commonly used and expensive atomic spectroscopic methods. The application of anodic stripping voltammetry for the determination of lead ion in locally produced cooking utensils and the increased levels of lead in the vegetables while cooking with the lead containing utensils is reported in this work.…”
Section: Introductionmentioning
confidence: 99%